Development of strut and tie models for continuous deep beams using topology optimization - Nagarajan, Praveen; Pillai, T. M. Madhavan (Journal of Structural Engineering, 2025)
Generally structural members can be broadly divided into two regions, namely B or Bernoulli regions where the strain distributions are linear and D or Disturbed regions where the strain distributions are nonlinear. Though the present design standards recommend well defined theories for designing B regions, the code provisions for D regions are empirical in nature. The strut and tie model can be used for the design of both B and D regions. In a deep beam, the distribution of strain across depth of the cross section will be nonlinear and hence these structural elements belong to D regions. Even though strut and tie model is effective for the design of deep beams, development of strut and tie models are difficult using the conventional methods. Topology optimization is an effective tool to overcome the above problem. In this paper, development of strut and tie models for continuous deep beams using topology optimization are discussed. The use of these models from a detailing point of view is also highlighted.